Analisis Framing Demonstran Indonesia Gelap dalam Bingkai Media CNN Indonesia dan Tempo.co - Zamardha, Meidita Helvy Rosa; Zuhri, Saifuddin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study analyzes CNN Indonesia and Tempo.co's coverage of the #IndonesiaGelap movement. News articles were analyzed from February 17 to April 8, 2025, to examine the ideological tendencies of each media outlet. Using qualitative methods with Robert N. Entman's framing analysis, as well as the theory of social reality construction and media political economy, the results of the study show that CNN Indonesia, as part of the Trans Media conglomerate, tends to be uncritical of the government, while Tempo.co applies watchdog journalism with a more critical stance. This study emphasizes the importance of independence and balance in journalism practices in Indonesia.